Courtship, Mating Behavior, and Ovary Histology of the Nymph Parasitoid Psyllaephagus bliteus (Hymenoptera: Encyrtidae) - Favoreto, A. L. [UNESP]; Domingues, M. M. [UNESP]; Serrão, J. E.; Ribeiro, M. F. [UNESP]; Silva, C. A.D.; Zanuncio, J. C.; Wilcken, C. F. [UNESP] (Oxford University Press (OUP), 2021)
The potential of the parasitoid Psyllaephagus bliteus Riek for the biological control of the eucalyptus pest Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae) nymphs is high. This research sought to analyze the courtship, male competition, and mating behavior of P. bliteus at the proportions of 1:1 and 2:1 males to female in a Petri dish (5 cm diameter), and to describe the ovary histology of virgin and mated females of this parasitoid. At 1:1, males touch the antennae and thorax-abdomen of females during courtship, but females avoid mate attempts before they are 48 h old. At 2:1, the competition between male parasitoids inhibits mating. The histology of ovaries of virgin and mated P. bliteus females is similar, with two well-defined germarium and vitellarium regions, with oocytes at different developmental stages, including mature ones rich in yolk and with eggshell. A clearer understanding of the reproductive behavior and histology of P. bliteus aids in the use of this parasitoid for the biological control of G. brimblecombei.
Keywords: biological control; mass rearing; nymph parasitoid; wing fanning